A simple technique to synthesize pure and highly crystalline boron nitride nanowires - Ahmad, P.; Khandaker, Mayeen Uddin; Khan, Z.R.; Amin, Yusoff Mohd (Elsevier, 2014)
Unlike various complex and extensive experimental procedures available in the literature, a simple experimental technique has been developed to synthesize boron nitride nanowires (BNNWs) on Si substrates in a short growth duration of 30 min via vapor–liquid–solid (VLS) growth mechanism. The surface morphology and diameter of BNNWs were obtained by field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HR-TEM). The as-grown boron nitride nanowires have a wire-like morphology with diameter in the range of ~20–150 nm. The Raman spectrum of the synthesized BNNWs showed a sharp and intense peak at 1380 (cm−1) corresponds to the E2g mode of vibration in h-BN depicted its highly crystalline nature. This work reveals that a modified CVD technique and short growth duration is suitable to synthesis nanowires with tens of nanometers in diameter.